RICOSRE FOR THE EMPOWERMENT OF STUDENTS’ SCIENTIFIC LITERACY IN A ISLAMIC BOARDING SCHOOL - Mohammad Taufik Aji Fahruli; Iqbal Bilgrami Biruni; Nindiana Choirunnisa’; Dewi Karomika; Mohammad Ali Sofyan; Aninda Yulianti Rahmana (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Scientific literacy skills are very important in the learning process and daily life. Scientific literacy does not arise suddenly but requires a facilitator who enables it. One of these is the application of learning models that have the potential to improve scientific literacy. A learning model that has the potential to improve science literacy skills is Problem-Based Learning one of which is RICOSRE. This study aims to investigate the effect of RICOSRE on the science literacy skills of grade X students compared to PBL and conventional models. This study involved 94 students from SMA Progresif Bumi Shalawat Sidoarjo, East Java, Indonesia, and employed a pretest-posttest design with a non-equivalent controls group. The pretest and posttest consisted of 8 essay questions each. ANCOVA and LSD tests to analyze student scores. The results indicated a significant effect of RICOSRE on the students’ scientific literacy skills. The student’s average score on scientific literacy skills increased considerably (45,23%) on RICOSRE and PBL (15.73%) and decreased in conventional learning by 4.57%. RICOSRE can be implemented to empower students' scientific literacy skills. These results indicate that RICOSRE is proven to be more effective in improving students' scientific literacy skills compared to PBL and conventional learning models.